2018
DOI: 10.1038/s41598-018-21059-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the similarity and difference of three influenza surveillance systems in China

Abstract: Three main surveillance systems (laboratory-confirmed, influenza-like illness (ILI) and nationwide Notifiable Infectious Diseases Reporting Information System (NIDRIS)) have been used for influenza surveillance in China. However, it is unclear which surveillance system is more reliable in developing influenza early warning system based on surveillance data. This study aims to evaluate the similarity and difference of the three surveillance systems and provide practical knowledge for improving the effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 19 publications
3
21
0
Order By: Relevance
“…It should be noted that another peak of RR in high temperature for Flu-A was observed in the study. This finding was supported by previous studies, which reported the semiannual epidemic in the summer in subtropical cities in China (Yang et al, 2018a;Yang et al, 2018b;Ye et al, 2019). The potential reasons for this semiannual epidemic required further research.…”
Section: Discussionsupporting
confidence: 87%
“…It should be noted that another peak of RR in high temperature for Flu-A was observed in the study. This finding was supported by previous studies, which reported the semiannual epidemic in the summer in subtropical cities in China (Yang et al, 2018a;Yang et al, 2018b;Ye et al, 2019). The potential reasons for this semiannual epidemic required further research.…”
Section: Discussionsupporting
confidence: 87%
“…The PVP increases with increasing specificity and prevalence. A similar study conducted in China to evaluate influenza surveillance emphasized laboratory-confirmed surveillance and sensitivity tools for developing influenza early warning systems (18).…”
Section: Discussionmentioning
confidence: 99%
“…The influenza surveillance system is a major data source for monitoring and evaluating the transmission and evolution of influenza 3032 . Two major surveillance systems, the Sentinel Influenza-Like Illness (ILI) Surveillance System and the Chinese Notifiable Infectious Diseases Reporting System (CNIDRS), have been widely used for influenza surveillance and research in China 16,30,33,34 .…”
Section: Introductionmentioning
confidence: 99%